Designing Mathematics Instruction Based on Problem-Based Learning to Improve the Mathematical Communication Skills of Eighth-Grade Junior High School Students - Faizah Tasya Nabila; Suyono; Lukman El Hakim; Tian Abdul Aziz (Universitas Teknokrat Indonesia, 2026)
This study aims to analyze the need to develop a Problem-Based Learning (PBL)-based mathematics instructional design to improve the mathematical communication skills of eighth-grade junior high school students. The study employed a descriptive approach and involved 31 eighth-grade students and a mathematics teacher at SMPN 2 Jakarta. Data were collected through observation, a mathematical communication skills test, a questionnaire, and interviews. The results of the study indicate that students’ mathematical communication skills remain low, particularly in constructing mathematical models, representing ideas in graphs, and explaining solutions in their own words. The average test score of 20.11 indicates that most students have not yet met the expected proficiency indicators. Furthermore, instruction remains teacher-centered, resulting in students being less active in communicating mathematical ideas. The results of the curriculum and conceptual analysis identified “Equations of Straight Lines” as a suitable topic to be developed through PBL-based instructional design. Thus, the results of this needs analysis serve as the basis for designing an instructional approach capable of facilitating the improvement of students’ mathematical communication skills.